2023
DOI: 10.3390/diseases11040163
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID and Physical Therapy: A Systematic Review

Juan Carlos Sánchez-García,
Andrés Reinoso-Cobo,
Beatriz Piqueras-Sola
et al.

Abstract: Prolonged COVID is a persistent condition following the initial COVID-19 infection, which is characterized by a variety of symptoms that may include fatigue, muscle pain, sleep disturbances, “brain fog”, respiratory, cardiovascular, digestive, neurological and dermatological symptoms. Physical therapy has been identified as a crucial aspect of the management of patients with long COVID, as it can help improve symptoms and overall physical function. The investigation of long COVID poses significant challenges d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
(42 reference statements)
0
4
0
3
Order By: Relevance
“…Sanchez-Garcia et al published a systematic review of studies of physical therapy in patients with long COVID. 11 They define prolonged COVID as a persistent condition characterized by fatigue, muscle pain, sleep disturbances, brain fog, and symptoms involving the cardiovascular, respiratory, digestive, neurologic systems. Their literature search eventually recovered 6 articles that were included in the review.…”
Section: Nopp Et Al Reported a Prospective Cohort Observational Study...mentioning
confidence: 99%
“…Sanchez-Garcia et al published a systematic review of studies of physical therapy in patients with long COVID. 11 They define prolonged COVID as a persistent condition characterized by fatigue, muscle pain, sleep disturbances, brain fog, and symptoms involving the cardiovascular, respiratory, digestive, neurologic systems. Their literature search eventually recovered 6 articles that were included in the review.…”
Section: Nopp Et Al Reported a Prospective Cohort Observational Study...mentioning
confidence: 99%
“…It is imperative that patients are counseled that this diverges fundamentally from conventional high intensity exercise regimens, which can induce PEM and be counterproductive. Conversely, a supervised, intentional regimen that diligently monitors physiological parameters and is carefully titrated to energy capacity can at a minimum prevent deconditioning, and if done well enhance mobility and aerobic function [45][46][47] . Cognitive rehabilitation, which can be facilitated by providers like speech-language pathologists or neuropsychologists, provides tailored assessments and can deliver evidence-based interventions for common PASC cognitive symptoms including aTention deficits and memory problems.…”
Section: : Energy Management and Prevention Of Post-exertional Malaisementioning
confidence: 99%
“…The symptoms associated with SARS-CoV-2 infections are varied and include not only fever, cough, and pulmonary diseases, but also gastrointestinal ailments and, at least in the case of pre-Omicron variants, neurological diseases, such as muscle soreness, headaches, dizziness, altered smell and taste as well as confusion and even psychiatric disorders [ 4 ]. Neurological symptoms are also a characteristic of the long COVID, a multisystemic syndrome that persists beyond the acute phase of the infection [ 5 ]. A clinical retrospective study reported that one-third of COVID-19 survivors presents neurological or psychiatric symptoms six months after the infection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Expected number of genes in the analyzed list for this category, based on the reference list 4. Fold enrichment of the genes observed in the analyzed list over the expected 5. Raw p-value as determined by Fisher's exact test 6.…”
mentioning
confidence: 99%